2015
DOI: 10.1002/2015ja021525
|View full text |Cite
|
Sign up to set email alerts
|

Plasma density undulations correlated with thermospheric neutral mass density in the daytime low‐latitude to midlatitude topside ionosphere

Abstract: Plasma density undulations in the dayside low‐latitude/midlatitude ionospheric F region were often attributed to thermospheric gravity waves (TGWs). However, the relationship between the former and the latter has been at best indirectly evidenced. In this study we investigate daytime fluctuations in neutral mass density (ρ) and plasma density (ne) measured onboard CHAMP from 2001 to 2010. A significant amount of daytime fluctuations in ne is strongly correlated with in situ fluctuations of ρ, which we term “TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Our present observations showed comparable results with the previous observations. The low occurrences during the equinoxes and summer are also similar to the results of Park et al (), Forbes et al (), and Liu et al ().…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our present observations showed comparable results with the previous observations. The low occurrences during the equinoxes and summer are also similar to the results of Park et al (), Forbes et al (), and Liu et al ().…”
Section: Discussionsupporting
confidence: 90%
“…Kotake et al (), Ding et al (), and Otsuka et al (, ) have reported that in the NH middle latitudes, the highest occurrence of daytime MSTIDs was during the winter (between November and February). Park et al () observed MSTIDs in a region between 300 and 400 km altitude, using the density measurements of the Challenging Minisatellite Payload (CHAMP) satellite. They observed the highest occurrence of MSTIDs over South America during the winter (June).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Largest perturbations are observed during June solstice months, an interval well overlapping with our study period. Park et al [2014Park et al [ , 2015 have shown the existence of thermospheric GW with horizontal wavelength of 150-600 km both on day and nightside. These GWs are believed to be driven from below because of their close spatial relation to GW activity centers in the stratosphere [e.g., Jiang et al, 2003].…”
Section: The Variability Of Current Densitymentioning
confidence: 99%
“…The in situ neutral mass density measurement of Challenging Minisatellite Payload (CHAMP) satellite showed high thermospheric gravity wave activity at the height of 300–400 km during daytime in winter solstice, which generally decrease from high latitudes to low latitudes (Park et al., 2014). Further, neutral mass density and plasma density measurements onboard CHAMP satellite showed a significant amount of daytime fluctuations in plasma density was strongly correlated with fluctuations of neutral mass density, particularly in the winter hemisphere, providing direct observation evidence to the cause and effect relationship between thermospheric gravity waves and ionospheric disturbances (Park et al., 2015). The high occurrence rate of periodic ionospheric disturbances at middle latitude in winter presented by this study is consistent with the high AGW activities at stratosphere/mesosphere/thermosphere at similar or higher latitudes of East Asia.…”
Section: Discussionmentioning
confidence: 94%